Exploring the Potential of Hemigraphis alternata Leaves: Docking and Molecular Dynamics Analysis Targeting Cyclooxygenase-2 (COX-2) - Yeni, Yeni; Mochamad Dicky Yanuar Mamba'ul Rohman; Supandi Supandi (EKSAKTA: Journal of Sciences and Data Analysis, 2025)
Cyclooxygenase-2 (COX-2) mediates various physiological responses, including inflammation. In traditional medicine, the leaves of Hemigraphis alternata are commonly used to treat inflammation. The leaves have yielded 22 secondary metabolites that have been isolated. The computational analysis was conducted to identify the compounds with the greatest affinity for COX-2. The molecular docking procedure using DOCK 6.9 and molecular dynamics simulations using GROMACS 5.1.2 were used to screen test compounds. DOCK 6.9 assessed grid scores and ligand-receptor interactions, whereas GROMACS 5.1.2 examined the interactions, Root Mean Square Deviation (RMSD), Root Mean Square Fluctuation (RMSF), Molecular Mechanics-Poisson Boltzmann Surface Area (MM-PBSA), hydrogen bonds, and radius of gyration. The validation of the docking method resulted in an RMSD value of less than 2 Å, indicating that the docking protocols are suitable for screening potential ligands. Phytol exhibited the most attraction compared to the test and reference substances (diclofenac sodium), with a grid score of -32.85 kcal/mol. The MM-PBSA analysis revealed that phytol exhibited a greater affinity than the reference, as evidenced by binding free energy of -36.259 kcal/mol. These data suggest that phytol has the potential to be investigated as a possible source for the generation of COX-2 inhibitors.